2018
DOI: 10.3390/resources7040087
|View full text |Cite
|
Sign up to set email alerts
|

A Relationship of Causal Factors in the Economic, Social, and Environmental Aspects Affecting the Implementation of Sustainability Policy in Thailand: Enriching the Path Analysis Based on a GMM Model

Abstract: This research aimed to analyze the influence of the direct and indirect relationships of economic, social, and environmental factors as well as predict their future effects by applying a path analysis of a generalized method of moments model (path analysis–GMM model). The model is believed to be the most effective in relationship analysis, as it is capable of accurate prediction compared to the original models. Most importantly, the model can be applied to different contexts, benefiting the development areas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Economic indicators include the gross domestic product (GDP) per capita, urbanization rate, industrial structure, net exports, and indirect foreign investment. In contrast, social indicators include employment, health and disease, social security, and consumer protection, negative and significant effects on the environment (Sutthichaimethee and Dockthaisong, 2018). GDP per capita and Exports increase CO2 emissions per capita (Cheng et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Economic indicators include the gross domestic product (GDP) per capita, urbanization rate, industrial structure, net exports, and indirect foreign investment. In contrast, social indicators include employment, health and disease, social security, and consumer protection, negative and significant effects on the environment (Sutthichaimethee and Dockthaisong, 2018). GDP per capita and Exports increase CO2 emissions per capita (Cheng et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The concept can be described as a Non-Recursive Vector autoregression based on an exogeneous model or "Non-Recursive Var-X" model. The research has utilized the linear structural relations (LISREL) model (Sutthichaimethee and Dockthaisong, 2018). As for its validity, the model was assessed by white noise testing and goodness of fit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a whole, this construct is called "Structural Equation Modeling-Vector Autoregressive with Exogeneous Variables Model" (SEM-VARIMAX Model). The research also utilizes Linear Structural Relations (LISREL) [93] software along with Econometric Views (EVIEWS) [94,95].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research flow is explained below, as shown in Figure 1. [93] software along with Econometric Views (EVIEWS) [94,95]. The above-mentioned model is assessed in term of its Model Validity and Best Modelling, as well as "Best Linear Unbiased Estimated (BLUE) assessment.…”
Section: Literature Reviewmentioning
confidence: 99%